Solid electrolyte membrane, cathode-free alkali metal battery interface layer and preparation method of cathode-free alkali metal battery interface layer
By using a cross-linked structure of solid electrolyte membrane and interface layer in an anode-free alkali metal battery, the problems of uneven alkali metal deposition and side reactions are solved, extending the cycle life of the battery and improving energy density and safety.
Patent Information
- Application Number
- CN202411254513.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-27
AI Technical Summary
The alkali metal deposition of negative electrode-free alkali metal batteries is uneven and has serious side effects, resulting in low efficiency of Coulomb and short cycle life, and there are commercial bottlenecks.
Using polymer molecular chains with flexible and alkaline metals with high mechanical strength and carboxymethylcellulose salts, they are cross-linked through hydrogen bond receptors provided by nano-metal oxygen clusters in polymetallic acid salts to form both rigid and soft The crosslinked structure forms the interface layer of solid electrolyte membrane and negative electrode-free alkali metal battery, promotes uniform deposition of alkali metal ions, forms a dense SEI layer, and alleviates the stress and side reactions caused by volume changes.
Effectively extend the cycle life of negative electrode-free alkali metal batteries, improve the energy density and safety of the battery, reduce costs, and improve Coulomb efficiency and circulation performance.
Smart Images

Figure CN119208719A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of alkali metal batteries, and in particular relates to a solid electrolyte membrane, an alkali metal battery interface layer without a negative electrode and a preparation method thereof, and an alkali metal battery without a negative electrode. Background Art
[0002] In the 21st century, with the increasing demand for electronic devices and energy storage, rechargeable secondary batteries have been widely developed as an energy storage device. In just a few decades, lithium-ion batteries have been highly commercialized and applied in many fields such as portable power supplies and new energy vehicles. At present, the energy density of lithium-ion batteries has reached its limit (300Wh kg -1 ), the pursuit of large-capacity and long-lasting devices has led to the research and development of higher energy density battery systems. Lithium metal batteries use lithium foil as the negative electrode, which has a very high theoretical specific capacity (3840mAh g -1 ), the lowest redox potential (-3.04Vvs standard hydrogen electrode), which can greatly improve the energy density of the battery from the negative electrode side, and is considered the "holy grail" negative electrode of the battery. The energy density of lithium metal batteries can reach 500Wh kg -1 , which is twice the energy density of existing commercial lithium-ion batteries. However, alkali metal batteries such as these often use a high N / P ratio (referring to the margin of the negative electrode capacity on the opposite side of the battery exceeding the positive electrode capacity under the same conditions) to improve cycle stability, resulting in a serious loss of energy density. Excessive alkali metals also significantly reduce the safety of the battery and bring a huge cost burden to alkali metal batteries.
[0003] In contrast, negative electrode-free alkali metal batteries have great potential to provide high energy density. For example, negative electrode-free lithium metal batteries are an iterative system of lithium metal batteries. On the basis of lithium-ion batteries, they eliminate the use of negative electrode active materials. During charging, lithium ions in the positive electrode active material combine with electrons on the surface of the current collector to deposit a layer of lithium metal; during discharge, the lithium metal on the surface of the negative electrode dissolves, passes through the electrolyte and returns to the positive electrode, and the cycle is repeated. Due to the lack of graphite and lithium foil as electrode materials, the cost of negative electrode-free lithium metal batteries is reduced, the safety is improved, and the energy density is greatly improved. However, due to electrolyte side reactions and uneven interfacial lithium deposition, the coulombic efficiency and cycle life of negative electrode-free alkali metal batteries are currently low, and there are still commercial bottlenecks. In order to improve the cycle life of negative electrode-free alkali metal batteries, strategies such as interface engineering, electrolyte engineering, and positive electrode sacrificial agents have been widely studied and applied. Among them, the current collector / electrolyte artificial interface is a good strategy. This ultra-thin interface layer can cover the surface of the current collector to form a dense functional deposition layer for relieving stress or inhibiting side reactions.
[0004] In the present invention, a flexible and alkali metal-philic polymer molecular chain is used with a carboxymethyl cellulose salt with high mechanical strength and large Young's modulus, and the hydrogen bond receptors provided by the nano-metal oxygen clusters in the polyoxometalate are cross-linked to form a "rigid and flexible" cross-linked structure, which can effectively alleviate the stress caused by volume change, promote the uniform deposition of alkali metal ions on the surface of the current collector, and form a dense SEI layer, thereby effectively extending the cycle life of the negative electrode-free alkali metal battery. In this interface layer, the alkali metal-philic polymer molecular chain provides active sites for the deposition of alkali metal ions, promoting their uniform electroplating on the surface of the copper foil; the carboxymethyl cellulose salt can effectively improve the ionic conductivity and ion migration number between the interface layers, and alleviate the volume change between the layers; the polyoxometalate as a nano-metal oxygen cluster contains rich hydrogen bond receptors, which can be combined with the functional groups in the above-mentioned chain structure through hydrogen bonds to form a dense cross-linked layer, and its higher ionic conductivity can also promote ion conduction. At the same time, the dense SEI layer can effectively inhibit further side reactions between the electrolyte and the alkali metal layer. Summary of the invention
[0005] In summary, the present invention aims to provide a solid electrolyte membrane, an alkali metal battery interface layer without a negative electrode and a preparation method thereof, so as to solve the above-mentioned problems such as uneven alkali metal deposition and serious side reactions, thereby effectively extending the cycle life of the alkali metal battery without a negative electrode.
[0006] In a first aspect, the present invention provides the use of carboxymethyl cellulose salts, polymer molecular chains, and heteropolyacid salts in solid electrolytes and alkali metal / negative electrode-free alkali metal battery interface layers.
[0007] In a second aspect, the present invention provides a solid electrolyte membrane formed by cross-linking carboxymethyl cellulose salt, polymer molecular chains and polyoxometalate through hydrogen bonds.
[0008] Furthermore, the solid electrolyte membrane has a polymer-metal oxide cluster-polymer cross-linked structure that is both rigid and flexible.
[0009] In a third aspect, the present invention provides an artificial interface layer for a negative electrode-free alkali metal battery, comprising a multiphase interface of "battery current collector / solid electrolyte membrane / electrolyte", wherein the interface layer is attached to the surface of the current collector, has a nanometer-level thickness, and is composed of the solid electrolyte membrane.
[0010] Furthermore, the battery current collector includes but is not limited to copper foil and other commonly used current collectors for batteries, and the interface layer includes but is not limited to alkali metals and negative electrode-free alkali metal batteries.
[0011] Furthermore, the alkali metal is usually one of lithium, sodium and potassium.
[0012] In a fourth aspect, the present invention provides a method for preparing an artificial interface layer of a negative electrode-free alkali metal battery, comprising:
[0013] The carboxymethyl cellulose salt, polymer molecules and polyoxometalate are mixed in a solvent in proportion to obtain a mixed solution.
[0014] After the mixed solution is stirred evenly, it is coated on the current collector by scraping and dried in an oven to obtain a negative electrode-free lithium metal battery interface layer containing the solid electrolyte membrane.
[0015] Furthermore, the carboxymethyl cellulose salt is one of lithium carboxymethyl cellulose (CMC-Li), sodium carboxymethyl cellulose (CMC-Na), and potassium carboxymethyl cellulose (CMC-K), and the degree of substitution is between 0.5 and 0.8; the polymer molecules include but are not limited to one or more of polyhydroxyethyl methacrylate (PHEMA), polyethylene oxide (PEO), and polytrifluoroethyl methacrylate (PTFEMA); the polyoxometalate is PMo 12 , PW 12 、SiW 12 One of the clusters; the solvent is deionized water or an ionic liquid.
[0016] Furthermore, the ratio of the polymer molecules to the carboxymethyl cellulose salt is (1-10):1, and the polyoxometalate accounts for 10%-100% of the total mass of the polymer molecules and the carboxymethyl cellulose salt.
[0017] Furthermore, the concentration of the mixed solution is (1-5) mg ml -1 , preferably 2 mg ml -1 , the drying temperature needs to be less than 60℃.
[0018] Furthermore, the current collector with the interface layer is perforated and can be used in various negative electrode-free lithium metal batteries.
[0019] In a fifth aspect, the present invention provides an alkali metal battery without a negative electrode, comprising the alkali metal battery interface without a negative electrode, or the solid electrolyte membrane.
[0020] It can be seen from the above technical solution that this method has the following advantages:
[0021] 1. The present invention provides the use of carboxymethyl cellulose salt, polymer molecular chain, and heteropoly acid salt in a solid electrolyte membrane or an alkali metal / alkali metal battery interface layer without a negative electrode; and provides a solid electrolyte membrane, wherein the solid electrolyte membrane is formed by cross-linking carboxymethyl cellulose salt, polymer molecular chain, and polyoxometalate through hydrogen bonds, and has a rigid and flexible polymer-metal oxygen cluster-polymer cross-linking structure. The hydroxyl groups in the carboxymethyl cellulose salt and the highly electronegative functional groups in the polymer molecular chain can act as hydrogen bond donors, and combine with the hydrogen bond acceptors provided by the polyoxometalate, thereby cross-linking into a dense solid electrolyte membrane. This rigid and flexible structure can effectively slow down the volume stress changes caused by lithium deposition.
[0022] 2. The carboxymethyl cellulose salt used in the present invention is usually carboxymethyl cellulose lithium (CMC-Li), which has a high ion migration number (0.66), a high Young's modulus (24.7GPa) and good lithium affinity, and can be used as an artificial SEI layer framework with a rigid structure. The dense and uniform interface layer formed by the CMC-Li macromolecular chain can effectively prevent lithium dendrites from piercing and regulate the volume expansion during lithium deposition.
[0023] 3. The polymer molecular chain used in the present invention is generally poly(2-hydroxyethyl methacrylate) (PHEMA), which has a strong lithium ion binding energy and thus has a strong lithium affinity. The unsaturated functional group ester group in the polymer side chain makes it have a large binding energy with lithium ions, and the lithium salt is more likely to dissociate, thereby promoting the kinetics of lithium ion migration and making it easier for metal lithium with a larger grain diameter to nucleate and grow.
[0024] 4. The polyoxometalates used in the present invention, such as lithium phosphotungstate, contain abundant hydrogen bond receptors and can be used as nanodots to crosslink the "soft phase" and "hard phase" polymer segments; they are easily soluble in water and have good compatibility with water. At the same time, the POM ion core in lithium phosphotungstate is conducive to Li + The jump transmission reduces Li + diffusion energy barrier.
[0025] 5. The interface layer provided by the present invention includes a solid electrolyte membrane containing a multiphase interface, which is attached to the surface of the current collector and has a nanometer-level thickness. Its ultra-thin thickness is conducive to improving the overall energy density of the battery.
[0026] 6. The present invention provides a method for preparing an artificial interface layer of an alkali metal battery without a negative electrode, comprising mixing carboxymethyl cellulose salt, polymer molecules and polyoxometalate in a solvent in proportion, stirring the mixture evenly, coating it on a current collector by scraping, and drying it in an oven to obtain an interface layer of a lithium metal battery without a negative electrode containing the solid electrolyte membrane. The viscosity provided by the polymer and carboxymethyl cellulose salt enables the dried mixture to form an ultra-thin interface layer on the copper surface, thereby allowing alkali metal ions to be evenly deposited during the battery cycle, thereby improving the cycle performance of the alkali metal battery without a negative electrode. The preparation method is simple, convenient and environmentally friendly, and can be used for large-scale production and promotion, which is conducive to the production and application of a new generation of alkali metal batteries without a negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to further explain the specific technical solutions in the present invention, the following is a brief introduction to the drawings required for use in the specific implementation methods:
[0028] Figure 1 It is a schematic diagram of the cross-linking of the “polymer-metal oxide cluster-polymer” solid electrolyte membrane.
[0029] Figure 2 This is a physical picture of the ultra-thin solid electrolyte interface film.
[0030] Figure 3 1mAcm -2 、1mAh cm -2 3. Comparison of the Coulombic efficiency of Li / / Cu half-cell for long cycles under the conditions of (bare Cu foil and Cu foil containing the interface layer).
[0031] Figure 4 2mAcm -2 , 2mAh cm -2 3. Comparison of the Coulombic efficiency of Li / / Cu half-cell for long cycles under the conditions of (bare Cu foil and Cu foil containing the interface layer).
[0032] Figure 5 Comparison of contact angles between electrolyte and bare Cu foil and modified copper foil (the electrolyte used was 1.0MLiPF6+0.02M LiDFOB+FEC:FEMC:HFE (v:v:v=1:3:1)).
[0033] Figure 6 Curves showing the change of specific capacity and coulombic efficiency over time of Cu / / NCM811 battery with bare Cu foil and Cu foil containing interface layer as electrodes at 0.2C charge rate and 0.5C discharge rate when the voltage is 3.0-4.6V. DETAILED DESCRIPTION
[0034] In order to better understand the present invention and more clearly explain the conditions and features of the present invention, the present invention will provide the following embodiments. Note: The following embodiments are examples for different application conditions and do not limit the content and protection scope of the present invention. Anyone who obtains a product similar or close to the present invention under the enlightenment of the present invention, or a similar product obtained by combining the method, technical features of the present invention with other technologies, all falls within the protection scope of the present invention.
[0035] The basic idea of the present invention is: through the action of hydrogen bonds, the polymer molecular chains of alkali metals are cross-linked with carboxymethyl cellulose salts and heteropolyacid salts with high Young's modulus to form a solid electrolyte membrane with a cross-linked structure that is both rigid and flexible, which effectively alleviates the stress caused by volume change; through the solid electrolyte membrane, it is attached to the surface of the current collector to promote the uniform deposition of alkali metal ions on the surface of the current collector; through an artificial interface layer coated on the surface of the current collector, the electrolyte forms a dense SEI layer on the surface of the current collector during the circulation process, thereby effectively extending the cycle life of the negative electrode-free alkali metal battery.
[0036] The lithium carboxymethyl cellulose in this embodiment is prepared from sodium carboxymethyl cellulose by a conventional substitution method, and the specific method is as follows:
[0037] (1) Sodium carboxymethyl cellulose was dispersed in a mixture of ethanol and water (volume ratio 90:10), treated with 20% hydrochloric acid for 2 hours, filtered after sufficient reaction, and washed with 95% ethanol for 3 times to obtain desubstituted carboxymethyl cellulose (CMC-H).
[0038] (2) The carboxymethyl cellulose was dissolved in a mixture of ethanol and water (volume ratio 90:10), and then treated with a 5% LiOH aqueous solution for 2 hours. After sufficient reaction, the mixture was filtered, washed with 95% ethanol for 3 times, and dried to obtain carboxymethyl cellulose lithium (CMC-Li).
[0039] The polyoxometalate in this embodiment, such as lithium phosphotungstate, can be prepared by ion exchange method as follows:
[0040] (1) At room temperature, weigh H3PW according to the stoichiometric ratio of 1:3. 12 O 40 · 28H2O and anhydrous LiCl, mix and place in a beaker, add deionized water to dissolve, and stir on a magnetic stirrer for 5 minutes.
[0041] (2) Add ammonia water dropwise to the mixed solution after the reaction. When the pH value measured by a pH meter is 6 to 7, stop adding ammonia water dropwise.
[0042] (3) The mixed solution was placed in an oven at 80° C. and dried for 3 h. The obtained white solid was washed with anhydrous ethanol and dried again to obtain a white powdery lithium phosphotungstate solid.
[0043] Example 1
[0044] A solid electrolyte, the preparation method of which is as follows:
[0045] (1) Under normal temperature and pressure, weigh 20 mg of lithium carboxymethyl cellulose (CMC-Li), 30 mg of poly(2-hydroxyethyl methacrylate) (PHEMA), and 50 mg of lithium phosphotungstate (Li3PW 12 O 40 ), the CMC-Li, PHEMA and Li3PW 12 O 40 Add to a glass container containing 20 ml of deionized water and mix thoroughly to obtain approximately 5 mg ml -1 of mixed solution.
[0046] (2) After stirring the mixture for 3 hours, pour it onto a polytetrafluoroethylene plate at room temperature.
[0047] (3) Drying the plate carrying the mixed solution in an oven at 60° C. for more than 24 hours to obtain the solid electrolyte film.
[0048] (4) The solid electrolyte is removed with tweezers and punched with a cutting machine. The solid electrolyte can be used for all-solid-state alkali metal / negative electrode-free alkali metal batteries.
[0049] Example 2
[0050] A negative electrode-free lithium metal battery interface layer, the preparation method of which is as follows:
[0051] (1) Under normal temperature and pressure, weigh 3 mg of lithium carboxymethyl cellulose (CMC-Li), 4 mg of poly(2-hydroxyethyl methacrylate) (PHEMA), and 3 mg of lithium phosphotungstate (Li3PW 12 O 40 ), the CMC-Li, PHEMA and Li3PW 12 O 40 Add to a glass container containing 5 ml of deionized water and mix thoroughly to obtain approximately 2 mg ml -1 of mixed solution.
[0052] (2) After stirring the mixed solution for 3 hours, the mixed solution was coated on the copper current collector using a disposable water pipette at room temperature.
[0053] (3) Drying the glass plate carrying the current collector in an oven at 60° C. for more than 12 hours to obtain an artificial interface layer containing the solid electrolyte membrane.
[0054] (4) Punch holes in the current collector with a cutting machine to obtain a current collector electrode containing an artificial interface layer. In a glove box filled with argon (water content <0.01ppm, oxygen content <0.01ppm), the artificial interface layer is combined with an electrolyte, a separator (PP / PE), a positive electrode sheet (NCM / LFP, etc.), a battery shell, a gasket, etc., to prepare a negative electrode-free lithium metal battery with good performance.
[0055] Example 3
[0056] A negative electrode-free sodium metal battery interface layer, the preparation method of which is as follows:
[0057] (1) Under normal temperature and pressure, weigh 3 mg sodium carboxymethyl cellulose (CMC-Na), 4 mg poly(2-hydroxyethyl methacrylate) (PHEMA), and 3 mg sodium phosphotungstate (Na3PW 12 O 40 ), the CMC-Na, PHEMA and Na3PW 12 O 40 Add to a glass container containing 5 ml of deionized water and mix thoroughly to obtain approximately 2 mg ml -1 of mixed solution.
[0058] (2) After stirring the mixed solution for 3 hours, the mixed solution was coated on the copper current collector using a disposable water pipette at room temperature.
[0059] (3) Drying the glass plate carrying the current collector in an oven at 60° C. for more than 12 hours to obtain an artificial interface layer containing the solid electrolyte membrane.
[0060] (4) Punch holes in the current collector with a cutting machine to obtain a current collector electrode containing an artificial interface layer. In a glove box filled with argon (water content <0.01ppm, oxygen content <0.01ppm), the artificial interface layer is combined with sodium ion battery electrolyte, diaphragm (PP / PE), positive electrode sheet (NCM / LFP, etc.), battery shell, gasket, etc. to prepare a negative electrode-free sodium metal battery with good performance.
[0061] Example 4
[0062] An artificial SEI interface layer for a lithium metal battery, used for a negative electrode of a lithium metal battery, and a preparation method thereof is as follows:
[0063] (1) Under normal temperature and pressure, weigh 3 mg of lithium carboxymethyl cellulose (CMC-Li), 4 mg of poly(2-hydroxyethyl methacrylate) (PHEMA), and 3 mg of lithium phosphotungstate (Li3PW 12 O 40 ), the CMC-Li, PHEMA and Li3PW 12 O 40 Add to a glass container containing 5 ml of deionized water and mix thoroughly to obtain approximately 2 mg ml -1 of mixed solution.
[0064] (2) After stirring the mixed solution for 3 hours, the mixed solution was coated on the copper current collector using a disposable water pipette at room temperature.
[0065] (3) Drying the glass plate carrying the current collector in an oven at 60° C. for more than 12 hours, and depositing 5 mAh of metallic lithium on the surface of the copper foil containing the interface layer by electroplating to obtain a lithium metal battery negative electrode containing the interface layer.
[0066] Example 5
[0067] A negative electrode-free lithium metal battery interface layer, the preparation method of which is as follows:
[0068] (1) Under normal temperature and pressure, weigh 2 mg of lithium carboxymethyl cellulose (CMC-Li), 5 mg of polyethylene oxide (PEO), and 3 mg of lithium phosphotungstate (Li3PW 12 O 40 ), the CMC-Li, PEO and Li3PW 12 O 40 Add to a glass container containing 5 ml of deionized water and mix thoroughly to obtain approximately 2 mg ml -1 of mixed solution.
[0069] (2) After stirring the mixed solution for 3 hours, the mixed solution was coated on the copper current collector using a disposable water pipette at room temperature.
[0070] (3) Drying the glass plate carrying the current collector in an oven at 60° C. for more than 12 hours to obtain an artificial interface layer containing the solid electrolyte membrane.
[0071] (4) Punch holes in the current collector with a cutting machine to obtain a current collector electrode containing an artificial interface layer. In a glove box filled with argon (water content <0.01ppm, oxygen content <0.01ppm), the artificial interface layer is combined with an electrolyte, a separator (PP / PE), a positive electrode sheet (NCM / LFP, etc.), a battery shell, a gasket, etc., to prepare a negative electrode-free lithium metal battery with good performance.
[0072] Example 6
[0073] A negative electrode-free lithium metal battery interface layer, the preparation method of which is as follows:
[0074] (1) Under normal temperature and pressure, weigh 3 mg of lithium carboxymethyl cellulose (CMC-Li), 4 mg of poly(2-hydroxyethyl methacrylate) (PHEMA), and 3 mg of lithium phosphomolybdate (Li3PMo) respectively. 12 O 40 ), the CMC-Li, PHEMA and Li3PMo 12 O 40 Add to a glass container containing 5 ml of deionized water and mix thoroughly to obtain approximately 2 mg ml -1 of mixed solution.
[0075] (2) After stirring the mixed solution for 3 hours, the mixed solution was coated on the copper current collector using a disposable water pipette at room temperature.
[0076] (3) Drying the glass plate carrying the current collector in an oven at 60° C. for more than 12 hours to obtain an artificial interface layer containing the solid electrolyte membrane.
[0077] (4) Punch holes in the current collector with a cutting machine to obtain a current collector electrode containing an artificial interface layer. In a glove box filled with argon (water content <0.01ppm, oxygen content <0.01ppm), the artificial interface layer is combined with an electrolyte, a separator (PP / PE), a positive electrode sheet (NCM / LFP, etc.), a battery shell, a gasket, etc., to prepare a negative electrode-free lithium metal battery with good performance.
[0078] Example 7
[0079] A negative electrode-free lithium metal battery interface layer, the preparation method of which is as follows:
[0080] (1) Under normal temperature and pressure, weigh 3 mg of lithium carboxymethyl cellulose (CMC-Li), 4 mg of poly(2-hydroxyethyl methacrylate) (PHEMA), and 3 mg of lithium phosphotungstate (Li3PW 12 O 40 ), the CMC-Li, PHEMA and Li3PW 12 O 40 Add to a glass container containing 10 ml of deionized water and mix thoroughly to obtain approximately 1 mg ml -1 of mixed solution.
[0081] (2) After stirring the mixed solution for 3 hours, the mixed solution was coated on the copper current collector using a disposable water pipette at room temperature.
[0082] (3) Drying the glass plate carrying the current collector in an oven at 60° C. for more than 12 hours to obtain an artificial interface layer containing the solid electrolyte membrane.
[0083] (4) Punch holes in the current collector with a cutting machine to obtain a current collector electrode containing an artificial interface layer. In a glove box filled with argon (water content <0.01ppm, oxygen content <0.01ppm), the artificial interface layer is combined with an electrolyte, a separator (PP / PE), a positive electrode sheet (NCM / LFP, etc.), a battery shell, a gasket, etc., to prepare a negative electrode-free lithium metal battery with good performance.
[0084] Example 8
[0085] A negative electrode-free lithium metal battery interface layer, the preparation method of which is as follows:
[0086] (1) Under normal temperature and pressure, weigh 3 mg of lithium carboxymethyl cellulose (CMC-Li), 4 mg of poly(2-hydroxyethyl methacrylate) (PHEMA), and 3 mg of lithium phosphotungstate (Li3PW 12 O 40 ), the CMC-Li, PHEMA and Li3PW 12 O 40 Add to a glass container containing 5 ml of deionized water and mix thoroughly to obtain approximately 2 mg ml -1 of mixed solution.
[0087] (2) After the mixed solution was stirred for 3 hours, it was coated on the carbon / conductive polymer current collector using a disposable water pipette at room temperature.
[0088] (3) Drying the glass plate carrying the current collector in an oven at 60° C. for more than 12 hours to obtain an artificial interface layer containing the solid electrolyte membrane.
[0089] (4) Punch holes in the current collector with a cutting machine to obtain a current collector electrode containing an artificial interface layer. In a glove box filled with argon (water content <0.01ppm, oxygen content <0.01ppm), the artificial interface layer is combined with an electrolyte, a separator (PP / PE), a positive electrode sheet (NCM / LFP, etc.), a battery shell, a gasket, etc., to prepare a negative electrode-free lithium metal battery with good performance.
[0090] Note that the above embodiments are only examples for the purpose of clear description and are not intended to limit the implementation methods, so other conditions may be varied on the basis of the above conditions. The specific conditions are not exhaustively listed here.
Claims
1. Application of polymers formed by cross-linking carboxymethyl cellulose salt, water-soluble polymer and polyoxometalate in solid electrolyte membranes.
2. A solid electrolyte membrane, characterized in that: It is formed by cross-linking carboxymethyl cellulose salt, polymer chain segments and polyoxometalate through hydrogen bonds.
3. The solid electrolyte membrane according to claim 2, characterized in that: It has a polymer-metal oxide cluster-polymer cross-linked structure that is both soft and hard, rigid and flexible.
4. A negative electrode-free alkali metal battery interface, characterized in that: The current collector attached to the battery has a current collector / electrolyte artificial interface layer with a nanometer thickness, and the interface layer is the solid electrolyte membrane described in claims 2-3.
5. A method for preparing an interface layer of an alkali metal battery without a negative electrode, characterized in that: include: The carboxymethyl cellulose salt, polymer molecules and polyoxometalate are mixed in a solvent according to a certain proportion. The mixed solution is stirred and then coated on the current collector by scraping, and dried in an oven to obtain a negative electrode-free alkali metal battery interface layer containing the solid electrolyte membrane. The current collector with the interface layer can be used for assembling various negative electrode-free alkali metal batteries.
6. The preparation method according to claim 5, characterized in that: include: The carboxymethyl cellulose salt is one of lithium, sodium and potassium salts, and the degree of substitution is between 0.5 and 0.8; the water-soluble polymer molecules include but are not limited to one or more of polyhydroxyethyl methacrylate (PHEMA), polyethylene oxide (PEO) and polytrifluoroethyl methacrylate (PTFEMA); the polyoxometalate is PMo 12 , PW 12 、SiW 12 One of the clusters.
7. The preparation method according to claim 6, characterized in that: The solvent is deionized water or ionic liquid, and the current collector includes but is not limited to copper current collector. The ratio of the polymer molecules to the carboxymethyl cellulose salt is (1-10):1, and the polyoxometalate accounts for 10%-100% of the total mass of the polymer molecules and the carboxymethyl cellulose salt.
8. A negative electrode-free alkali metal battery, characterized in that: It comprises the interface described in claim 4, or comprises the interface layer prepared by the method according to any one of claims 5 to 7.
Citation Information
Patent Citations
Pegylation polyoxometallate and preparation method thereof
CN103145978A
Solid polymer lithium ion battery positive electrode and preparation method and application thereof
CN111554895A
Lithium battery diaphragm, preparation method thereof and lithium battery
CN117039341A
Modified current collector, preparation method thereof and non-cathode sodium battery
CN117747848A
Solid polymer electrolyte, solid polymer electrolyte membrane, and fuel cell
JP2004186120A
Cited By
Interface modification current collector, preparation method and cathode-free lithium metal battery
CN121460590A
